Chemical variability in Amazonian palm fruits: açaí (Euterpe oleracea Mart.), buriti (Mauritia flexuosa L. f.), and inajá [Maximiliana maripa (Aubl.) Drude] (Arecaceae) - Becker, Magda Márcia; Chagas, Vinicyus Teles; Marty, Jean-Louis; Mendes, Teresa Maria Fernandes de Freitas; Nunes, Gilvanda Silva (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
The bromatological composition, mineral content, bioactive compounds, and antioxidant capacity of three native Amazon Arecaceae fruits (buriti, açaí, and inajá) were chemically evaluated. These fruits showed high moisture contents (> 55%), and levels of ash values, total crude protein, and total carbohydrates in the range of 0.68-1.28%, 0.49-2.14%, and 6.10-26.51%, respectively. High levels of total lipids were found in buriti (21.0%). A wide range of mineral content was detected and the highest levels were found in the pulps of buriti (Ca, Cu, Fe, and Mg), inajá (Na and Zn) and açaí (Mn). All three fruits showed antioxidant activity with important levels of phenolic compounds and good or rich content of vitamin C. This study provides new data on the antioxidant activity and the nutritional composition of native Amazonian fruits. Based on this study, these fruits are suitable for use in the food and cosmetics industries, as well as in pharmaceutical compositions.
Keywords: Native Amazonian fruits; Bromatological composition; Minerals; Antioxidant capacity